Faktor yang Mempengaruhi Kunjungan Ibu Hamil Usia 28 Minggu di PMB Bina Marsasi Palembang Tahun 2024 - Marsasi, Bina; Julia, Dina; Qur’andini, Dalinur; Magumi, Novita (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Antenatal care (ANC) is monitoring the pregnancy to determine the general health of the mother, enforce accompanying disease early pregnancy, complications of pregnancy and pregnancy risks set. The purpose of this study to determine the factors that affect the visit pregnant women age ? 28 weeks at the PMB Bina Marsasi Palembang type of research used in this study is the author of analytic cross sectional survey. The population in this study were all pregnant women checkups in March 14 to April 2024 samples in this study were 30 pregnant women, based on the results of the univariate analysis of the 30 respondents, visit pregnant women good as many as 20 people (66.7%) and less visits as many as 10 people (33.3%), age at risk as many as 6 people (20%) and the ideal age as many as 24 people (80%), higher education as much as 17 people (56.7%) and low education were 13 persons (43.3%), high parity of 7 people (23.3%) and low parity as many as 23 people (76.7%), good knowledge of as many as 26 people (86.7%) and lack of knowledge as much as 4 people (13.3%), while the results of the bivariate analysis with the chi-square test p = 0.674 obtained> ? = 0.05 means that there is no relationship of age to visit pregnant women, p = 0.446> ? = 0.05 means that there is no relationship of education to visit, p = 0.571> ? = 0.05 means no parity relation to the visit, and p = 0.95> ? of 0.05 indicates no relationship to the knowledge of pregnant women visit . PMB Bina Marsasi can further enhance pemverian information to all pregnant women in the PMB Bina Marsasi about the importance of prenatal care. So that all pregnant women understand the benefits and danger signs during pregnancy.